2022
DOI: 10.3390/ijerph19074103
|View full text |Cite
|
Sign up to set email alerts
|

Openness to Experience Moderates the Association of Warmth Profiles and Subjective Well-Being in Left-Behind and Non-Left-Behind Youth

Abstract: Crouched in the socioecological framework, the present research compared the subjective well-being of left-behind youth with their non-left-behind peers. Furthermore, this research investigated the association of parental warmth and teacher warmth using a person-centered approach with adolescents’ subjective well-being on the whole sample, and examined its conditional processes by ascertaining the moderating role of openness to experience and left-behind status in this association. A total of 246 left-behind y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The average score of these items was calculated, with high values indicating higher levels of global life satisfaction. According to prior research (54), the MSLSS has demonstrated good internal consistency in Chinese adolescents. In this study, Cronbach's alpha was 0.93.…”
Section: Subjective Wellbeingmentioning
confidence: 96%
“…The average score of these items was calculated, with high values indicating higher levels of global life satisfaction. According to prior research (54), the MSLSS has demonstrated good internal consistency in Chinese adolescents. In this study, Cronbach's alpha was 0.93.…”
Section: Subjective Wellbeingmentioning
confidence: 96%
“…Personality traits (i.e., neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) can constantly demonstrate an individual’s behavioral patterns and thus has been widely adopted to interpret athlete performance ( Piepiora, 2021a , b ; Piepiora et al, 2021 , 2022 ). Among the big-five personality traits, a widely proved significant predictor of subjective well-being is openness to experience ( Dong and Ni, 2020 ; Ma et al, 2022 ; Tucaković and Nedeljković, 2022 ), i.e., an individual’s willingness to explore, tolerate, and consider new and unfamiliar ideas and experiences ( McCrae and Costa, 1987 ).…”
Section: Introductionmentioning
confidence: 99%